Morphometric analysis of pancytokeratin-negative neoplastic damages of the lymphatic nodes of the neck. - O. V. Poslavska; I. S. Shponka; P. O. Gritsenko; O. A. Alekseenko (Medičnì Perspektivi)
Patients with a diagnosis of cancer with an unknown primary localization (CUPL) are mostly referred to the category of cancer cohort with the clinical manifestation of lymph nodes enlargement. Cases of CUPL occupy 3-5% of all neoplasia of any localization, and only 20% of them have prognostically better chances as compared to other 80%. Materials and methods. The retrospective study 41 observations of the neoplastic lymph nodes in the neck without other clinical manifestations of primary tumor localization during was performed August 2016 - July 2017. The average age of patients was 47.68±16.41 years (median 46). The aim of the study was to analyze the complex of morphological, morphometric and immunohistochemical characteristics of Cytokeratin, Ran negative phenotypes of neoplastic lesions of lymph nodes of the neck for the improvement of diagnostic algorithms. Results. The authors have adjusted the objective parameters of nuclei of tumor cells (area, perimeter, coefficient of "roundness"), in comparison with the size of ordinary lymphocytes, the dependence of the size of the nuclei on morphological characteristics and the immunophenotype of the neoplastic damage of the lymph nodes of the neck has been analyzed.